Stan infrastruktury transportowej i bazy noclegowej w kontekście Mistrzostw Europy w Piłce Nożnej EURO 2012 = Transport infrastructure and accommodation in the context of the UEFA European Football Championship EURO 2012 - Gilewska, Katarzyna; Rabant, Hubert (Journal of Education, Health and Sport, 2015)
Gilewska Katarzyna, Rabant Hubert. Stan infrastruktury transportowej i bazy noclegowej w kontekście Mistrzostw Europy w Piłce Nożnej EURO 2012 = Transport infrastructure and accommodation in the context of the UEFA European Football Championship EURO 2012. Journal of Education, Health and Sport. 2015;5(5):253-262. ISSN 2391-8306. DOI 10.5281/zenodo.17699 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A253-262 https://pbn.nauka.gov.pl/works/560242 http://dx.doi.org/10.5281/zenodo.17699 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Stan infrastruktury transportowej i bazy noclegowej w kontekście Mistrzostw Europy w Piłce Nożnej EURO 2012 Transport infrastructure and accommodation in the context of the UEFA European Football Championship EURO 2012 Gilewska Katarzyna, Rabant Hubert1 1Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie: Niniejsze opracowanie związane jest z międzynarodową imprezą sportową, jaką były Mistrzostwa Europy w piłce nożnej, organizowane przez Polskę i Ukrainę w 2012 roku. Artykuł omawia stanu infrastruktury transportowej w Polsce oraz wielkości bazy noclegowej w miastach gospodarzach Mistrzostw Europy w piłce nożnej Euro 2012. Zakres pracy obejmuje jednak wyłącznie polską część Mistrzostw. Wskazano poziom realizacji przygotowań Polski do organizacji turnieju. Przestawiono też m.in. liczby udzielonych noclegów w 2012 r. w czterech miastach gospodarzach mistrzostw oraz dane statystyczne z działalności lotnisk w czasie turnieju. Abstract: This study is associated with an international sporting event, which was UEFA European Football Championship, organized by Poland and Ukraine in 2012. The article discusses the state of transport infrastructure in Poland and the size of accommodation in the cities - hosts of the UEFA European Football Championship Euro 2012. The scope of work includes but only the Polish part of the Championship. Indicated the level of implementation of Polish preparations to host the tournament. The section also includes among other things, the number of overnight stays in2012 in four cities as well as statistical data on the activities of the airports in the tournament. Słowa kluczowe: Euro 2012, infrastruktura transportowa, baza noclegowa. Keywords: Euro 2012, transport infrastructure, accommodation.